High mortality in dairy calves by neonatal diarrhea caused by Cryptosporidium sp associated with bacteremia in a dairy farm in Lima - Sandoval M., Rocío (2017)
This paper presents and discusses the clinical and pathological findings of an outbreak of neonatal diarrhea that caused a high mortality in a dairy farm in Lima, Peru. The diarrheas did not respond to antibiotics and occurred in calves less than one month old. The animals showed signs of dehydration, fluid feces, fever and marked depression of sensory. They were negative for coronavirus and rotavirus but were positive for Criptosporidium sp. In the post mortem study, a severe diffuse acute mucohemorrhagic enterocolitis was found and the histopathological diagnosis corroborated that it was a severe acute diffuse catarrhal enteritis associated with Cryptosporidium sp and bacterial nests. In the barn was found deficiencies in the management of colostrum and hygiene of the containers in which the milk was offered to the calves. The problem was solved introducing a series of good practices in calf handling.